THE EFFECT OF SCRAMBLE GAME ON THE ABILITY OF WRITING ENGLISH WORD OF THE 7TH GRADERS OF SMP ISLAM MA’ARIF 02 MALANG - Noor Fadhilah Damanhuri (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: Writing is one of the English skills that must be mastered by students. In this usage, the writer uses the scramble game technique as a learning method for students’ ability in word writing. In this case, the technique is used to make it easier for students to write words correctly.The research design in this study used a quantitative research design, a quasi-experimental design. Class VII consisted of 50 students and was divided into two groups, namely the experimental and control groups, where each group consisted of 25 students. The treatment given to the experimental group was using scramble games to write students’ words. The research gives a test instrument to students who must answer questions to measure students' achievement.To analyze the data, the research uses SPSS 20, namely the Independent T-test. The results showed that the average of the experimental group was (M= 77, 60) and the control group was (M= 66, 40). At the same time, the p-value of 0.000 (p < 0.05) was shown. After knowing the data results, it shows that there is a positive effect on the use of scramble game techniques in writing students’ words.Keywords: Scramble game, scramble word, writing ability